EPIZOOTIC PECULIARITIES OF DOG DEMODECOSIS IN THE TOWN OF POLTAVA - Kravchenko, S. O.; Melnychuk, V. V.; Kanivets, N. S.; Burda, T. L. (Scientific Progress & Innovations, 2020)
Demodecosis invasion is one of the most wide-spread dog acarine diseases irrespective of animal age, sex, and breed. It is known that the disease can be caused by several tick species, such as Demodex canis (Leydig, 1859), Demodex injai (Desch & Hillier, 2003), and Demodex sp. cornei. These ticks somehow differ from each other as to their morphological structure, localization place, however, they are united by ex-pressed pathological influence affecting dog organism. In most cases the disease is chronic and is treated with difficulty leading to considerable economic losses. Though the disease is wide-spread, many problems connected with epizootology have remained insufficiently studied, which complicates developing the measures of fighting and preventing the disease in several regions. That is why the aim of the research was to establish the spreading of dog demodecosis in the town of Poltava, the regularities of age dynamics, and also breed susceptibility.The study was conducted in the laboratory of the Department of parasitology and veterinary-sanitary expert examination and veterinary clinic of private entrepreneur Lokes-Krupka T. P. at the Department of therapy named after Prof. P. I. Lokes at Poltava State Agrarian Academy. Demodecosis was diagnosed using the improved technique of V.O. Yevstafieva and others, applying the mixture of bis-chofite and glycerin, one part to one. 562 dogs of twelve breeds (utility, hunting and decorative) and non-pedigree animals were subjected to acarological examination. The dogs were divided into five age groups (to one year of age, from one to three, from three to six, from six to nine, and more than nine years old). During the studies it has been established that dogs in Poltava are infected with Demodex canis, Leydig, 1859 demodecosis causative agent. Prevalence of infection made 7.29 %, on the average. It has been proven that the age of dogs considerably affects the index of infection. The maximum prevalence of infection was registered in dogs of two age groups – from 1 to three and older than 9 years of age (ЕІ=33.49 and 29.14 %, respectively). The dogs younger than 12 months were the least infected (ЕІ=18.45 %). According to the re-search results, it has been established that the indices of the prevalence of demodecosis infection depended on dogs’ breed peculiarities. Hunting and non-pedigree animals turned out to be the most infected with de-modecosis causative agent. The infection index of hunting breeds made 41.46 %, while it was 26.83 % in non-pedigree dogs. The animals of decorative breeds were the least susceptible to the disease, the average prevalence of infection in this group made 12.21 %.